Marketing Gozo as an idividual destination - Lazarova, Pauline (2009)
The island of Gozo for many years has received the unofficial status of second best, the aim of this paper is to determine and highlight the opportunities and problems the island faces in the current socio-economic climate and the possible long term benefits of positioning Gozo as a destination on its own merit. Interviews conducted with industry professionals together with use of analyses and research based on data obtained from mainstream travel agents and government institutions. Gozo has the potential and ability to sustain its self as an island destination and benefit the community and local economy through a variety of programmes aimed at capitalising on the unique features and attractions the island has at its disposal. The Island has the ability to be developed as a region destination through careful and planed use of its attributes, the development and promotion of niche segment attractions targeting specific groups of travellers. Expand the employment opportunities for local work force. Improve the social and economic status of the community through restructuring its tourism product, thereby attracting new investment and setting Gozo as a separate destination on the map.